Cape Verde : Background Issues and Statistical Update. (IMF Staff Country Reports; Country Report, 1995)
This Background Issues paper analyzes the financial sector reform in Cape Verde. The paper highlights that monetary policy in Cape Verde is conducted within the framework of a simple financial program elaborated annually by the Bank of Cape Verde (BCV) on the basis of conservative projections of the demand for broad money and an international reserves target. Credit to the government is statutorily limited to 10 percent of the previous year's revenue collections. In implementing monetary policy, the BCV relies primarily on bank-specific annual credit ceilings, which are derived from its financial program.